2008
DOI: 10.1164/rccm.200711-1739oc
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Control in Neonatal Rats Exposed to Prenatal Cigarette Smoke

Abstract: We show that prenatal CS exposure increases the likelihood of gasplike respiration and provide the first experimental evidence that the combined effects of prenatal CS exposure and hyperthermia dramatically prolong the time required for neonates to return to eupneic breathing after hypoxia. These observations provide important evidence of how prenatal CS exposure, hypoxic episodes, and hyperthermia might place infants at higher risk for sudden infant death syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 47 publications
5
37
0
Order By: Relevance
“…As previously reported in similar studies (Carmines and Rajendran, 2008; Pendlebury et al, 2008; Tachi and Aoyama, 1983), the pups of the exposed mothers had lower body weight than that of the controls at birth (5.77 ± 0.15 g vs. 6.66 ± 0.12 g ( P < 0.0001) in the two litters of each group in which this was measured), and their growth over the first four postnatal days was slower as well (3.74 ± 0.17 g vs. 4.64 ± 0.25 g; P < 0.005).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As previously reported in similar studies (Carmines and Rajendran, 2008; Pendlebury et al, 2008; Tachi and Aoyama, 1983), the pups of the exposed mothers had lower body weight than that of the controls at birth (5.77 ± 0.15 g vs. 6.66 ± 0.12 g ( P < 0.0001) in the two litters of each group in which this was measured), and their growth over the first four postnatal days was slower as well (3.74 ± 0.17 g vs. 4.64 ± 0.25 g; P < 0.005).…”
Section: Resultssupporting
confidence: 84%
“…Several previous studies have shown that gestational exposure to cigarette smoke retards fetal growth, resulting in low birth weight in both rats and humans (Bailey and Byrom, 2007; Esposito et al, 2008; Gaworski et al, 2004; Pendlebury et al, 2008). Our data are consistent with this finding and also show some reduction in the rate of postnatal growth in pups of gestationally smoke-exposed dams.…”
Section: Discussionmentioning
confidence: 99%
“…Few urothelial cells like crystals, cast, necrotic debris, mild inflammatory cells, transitional epithelium and squamous epithelium were observed consistently in most of the urine smears in the control group who are non-cigarette smokers which is in agreement with [12]. According to [13], cigarette smoking has been one of the leading causes of preventable death and a major public health concern, cigarette smoking causes most of the commonly diseases affecting the heart, lungs and the renal system [14]. In this research study, High cellular turnover was detected among 140 (70%) of the test group, this is due to the fact that when smokers inhale some of the carcinogens (cancer causing chemicals) in cigarettes, smokes are absorbed from the lungs and get into the blood, and from the blood, they are filtered by the kidneys and they are concentrated in urine in the bladder, thereby damaging the cells that line the inside of the bladder, leading to high cellular turnover and eventually causing bladder cancer, depending on how often and how long an individual continues to engage in cigarettes smoking.…”
Section: Discussionsupporting
confidence: 71%
“…We hypothesized that, in mouse neonates, raphe neurons, which express functional nicotinic acetylcholine receptors (31,32), could be targeted by prenatal-perinatal nicotine exposure, affecting their activities, their electrical properties, and their chemosensitivities. We studied CF1 neonates at Postnatal Days 1 (P1) to P8, because it is known that, within this period, prenatal cigarette smoke disrupts eupneic breathing and the ventilatory response to hypoxia in rats (33), whereas prenatal-perinatal nicotine exposure impairs ventilatory responses to hypercapnia and depresses central respiratory chemoreception in mice (19,30). Therefore, we expect that the diminished hypercarbiainduced ventilatory responses that occur in nicotine-exposed mice at P1-P3 will be accompanied at the same time by changes in the electrical properties or CO 2 responsiveness of raphe neurons, including both the serotonergic and nonserotonergic populations.…”
mentioning
confidence: 99%